The visible Flâneuse in Chan Ling Yap’s Where the Sunrise is Red - Nurul Atiqah Amran,; Arbaayah Ali Termizi, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Malaysia’s historical image in literature has almost always been exotically depicted. In some parts of literary works, geographical and physical settings serve merely as a literary device. The overwhelming depictions of characters’ geographical movements and relationship with their cities in the novel, Where the Sunrise is Red sparks the current resurgence to explore the visibility of the female protagonists in terms of their representations in the public sphere. Thus, the extent to which their representations are central to the development of the narration is debatable and to understand this; we must take into consideration Baudelaire’s construction of European urban figure, flâneur, emphasising the female version, the flâneuse. Different locations in colonial Malaysia and England seem to be the manifold literary device with which Yap develops her plots, yet the focus will be only at the crucial public domain that invites stares, barriers, and perceptions through the eyes and feelings of the character. Besides emphasising the characterisation of the protagonist, this setting is also symbolic of the underlying themes in the novel. The various public spheres where the protagonist is physically and visibly connected depict the reconstruction of a flâneuse in Malaysia’s historical representation in literature. Hence, the objectives of this study involve identifying the role of the public sphere and elaborating how these settings serve as the platform for flâneuse’s visibility in the Asian context through characterisation, physical setting, and symbols in the text.